Folic acid and acute diarrhea in children - Ade Amelia; Atan Baas Sinuhaji; Supriatmo Supriatmo (Paediatrica Indonesiana, 2014)
Background Diarrhea has been a health problem in childrenunder five year old. Although the mortality caused by acutediarrhea has fallen worldwide, the mortality has increased indeveloping countries, such as Indonesia.Objective To assess the effect of folic acid in reducing the severityof acute diarrhea in children.Methods This study was a single-blind, randomized control trialin children with diarrhea aged six months to five years at a localgoverrnent clinic in the Secanggang District, Langkat Regency,North Sumatera Province from August 2009 until January20 10. Subjects were recruited by con secutive sampling thenrandomized into two groups. Of the 112 children who participated,56 children received oral fo lic acid and 56 children receivedplacebo, 1 capsule per day for five days. The statistical analysesused were the independent T-test and Chi square test with 95%confidence intervals (95% CI) and P values < 0.05 consideredto be statistically significant.Results There were significant differences between the fo lic acidand placebo groups with regards to stool consistency (P=0.02),diarrheal volume on the second day [ 14 7 .52 vs. 303 .21 mL,respectively, (P=0.001)], frequency of diarrhea on the third day[1.9 vs 2.8 episodes, respectively, (P= 0.001)], duration of initialtreatment to recovery [91.3 vs. 117 .9 hours, respectively, (P =0.001) and the total duration between initial symptoms andrecovery (123.6 vs . 147.4 hours, respectively, (P = 0.001)].Conclusion Oral folic acid is clinically beneficial for reducing theseverity of acute diarrh ea in children under five year old.